Renewable DG allocation in radial distribution networks for techno-economic analysis using Chaotic Quasi Oppositional Arithmetic Optimization Algorithm - Dey, Indrajit; Roy, Provas Kumar (Measurement : journal of the International Measurement Confederation, 2025)
This paper introduces a chaotic quasi-oppositional arithmetic optimization algorithm (CQOAOA) for the placement and sizing of renewable distributed generators (DG) with the objective of active power loss minimization, annual operation costs reduction, and pollutant gas emissions mitigation and a multi-objective task of simultaneous optimization of annual operating costs and pollutant gas emissions are taken into consideration. The proposed CQOAOA algorithm is an improved version of arithmetic optimization algorithm (AOA). Here, two renewable energy sources solar and wind energy are used as DG where wind speed variation and solar irradiation are considered. The effectiveness of CQOAOA is exhibited on 33-bus, and 94-bus (Portuguese system) radial distribution networks (RDN). The percentage improvement obtained by CQOAOA algorithm with the objective of real power loss mitigation, pollutant gas emissions reduction, annual operation cost minimization are 58.69%, 99.94%, 22.30% for 33-bus system and 77.81%, 99.98%, 21.44% for 94-bus system respectively. •This paper presents a chaotic quasi-oppositional arithmetic optimization algorithm.•The CQOAOA is used for solving the renewable DG allocation problems of RDN.•Two renewable energy sources, photovoltaic (PV) and wind turbine (WT) are used as DG.•The performance of CQOAOA is tested on 33-bus and 94-bus radial distribution systems.•The superiority of CQOAOA is verified and compared with other algorithms.